A new genus and a new subgenus of cavernicolous beetles from Furong Jiang valley, southwestern China (Coleoptera: Carabidae: Trechinae). Issue 4 (4th July 2017) - Huang, Sunbin; Cen, Yijing; Tian, Mingyi
Summary: A new genus and a new subgenus of semi-aphaenopsian trechine beetles are described from Furong Jiang valley in the bordering areas of Chongqing Shi (Municipality) and Guizhou Province, southwestern China: Deuveaphaenops Tian & Huang, n. gen . (type species: Deuveaphaenops qimenxicus Tian & Huang, n. sp . from Qimenxia Cave II, Wulong Xian, Chongqing) and Furongius Tian & Huang, n. subgen . (type species: Deuveaphaenops ( Furongius ) gelaophilus Tian & Huang, n. sp . from cave Xianmi Dong, Daozhen Xian, Guizhou). Deuveaphaenops probably belongs to the complex of Cathaiaphaenops, Qianotrechus, Guizhaphaenops and Sinotroglodytes .